The efficacy and safety of dydrogesterone for treatment of dysmenorrhea: An open‐label multicenter clinical study. Issue 1 (23rd September 2018) - Taniguchi, Fuminori; Ota, Ikuko; Iba, Yumiko; Toda, Toshiko; Tagashira, Yukiko; Ohata, Yorie; Kurioka, Hiroko; Endo, Yusuke; Sunada, Hiroshi; Noma, Hisashi; Azuma, Yukihiro; Harada, Tasuku
Abstract: Aims: Dydrogesterone is a retro‐progesterone preparation widely used for over a half century. We sought to evaluate the efficacy and safety of dydrogesterone in Japanese women with dysmenorrhea. Methods: This study was conducted as an open‐label, single‐arm, multicenter study. One dydrogesterone 5‐mg tablet (Duphaston) was administered orally twice daily for 21 days from the 5th to 25th day of each menstrual cycle. A total of 44 (safety analysis) and 31 patients (efficacy analysis) were enrolled. Total dysmenorrhea score, dysmenorrhea subscale scores, dysmenorrhea visual analog scale, severity of menstruation‐related lower abdominal pain, low back pain, headache, and nausea/vomiting, basal body temperature, and serum estradiol and progesterone levels were evaluated. Results: Baseline of the total dysmenorrhea score was 4.61, which went down over time following the administration of dydrogesterone, and the decrease was statistically significant at and after 2nd cycle of menstruation. Mean change from baseline at the final evaluation point was −1.84 ( P < 0.001). Severity of menstruation‐related lower abdominal pain, low back pain, headache, and nausea/vomiting, in the evaluated menstruation cycles tended to decrease over time. Basal body temperature showed a biphasic pattern in 70% at baseline, 50% in 2nd menstruation cycle, and 61% in 5th menstruation cycle, and at least half of the patients may have had ovulation during the treatment. Incidence of adverse drug reactions was 31.8%, and the most common adverse event was metrorrhagia. Conclusion: Dydrogesterone is efficacious, safe, and clinically beneficial in patients with dysmenorrhea, thereby indicating that dydrogesterone can be considered as a treatment option for patients with dysmenorrhea.